Effect of fat replacement by chitosan and golden flaxseed flour (wholemeal and defatted) on the quality of hamburgers. (March 2019) - Hautrive, Tiffany Prokopp; Piccolo, Jaqueline; Rodrigues, Angela Souza; Campagnol, Paulo Cezar Bastianello; Kubota, Ernesto Hashime
Abstract: In this study, the effect of fat replacement by chitosan (CH), golden flaxseed wholemeal (GFW) and defatted golden flaxseed flour (DGF) on the physico-chemical, sensory and oxidative characteristics of hamburgers was evaluated. The following treatments were prepared: Control (10% fat); HCH (6% fat and 4% CH); HGFW (2.5% fat and 7.5% GFW) and HDGF (2.5% fat and 7.5% DGF). The formulation with the highest hardness, springiness, cohesiveness, fat retention and pH (6.65) and with the lowest shrinkage was the HCH. The hamburgers with chitosan presented lower sensory quality. However, the replacement of fat by GFW and DGF did not impair the sensory quality of hamburgers. The L * and a* values were seen to have a tendency to decrease while the b* and h* values tended to increase during the storage of hamburgers. Except for the GFW, the hamburgers presented TBARS values below 1.4 mg malonaldehyde.Kg −1 . The hamburgers prepared presented good physical-chemical characteristics. Highlights: Chitosan and golden flaxseed flour were used as fat replacer in hamburgers. Chitosan improved the technological and nutritional quality of low fat hamburgers. Reformulated hamburgers presented lower sensory acceptance. Hamburgers with food fibers and low fat content presented good physical-chemical.